Net neutrality: Prioritization is beneficial from an economic perspective - Pio Baake; Slobodan Sudaric (DIW Weekly Report, 2018)
The principle of net neutrality was adopted by the European Union as a regulation promoting equality among all data packets in the Internet. Considering net neutrality from a purely economic viewpoint, however, the general possibility to prioritize data packets would likely lead to a more efficient use of existing network capacity. This is particularly applicable given the growth in data traffic and time-sensitive applications such as live streaming. Competition among network operators could intensify if they had the possibility to differentiate their offers more finely-and private households would be the primary beneficiary. However, modifications in the spirit of net neutrality must go hand in hand with a clear commitment to competition law and its enforcement. Access to prioritization of individual data packets must be transparent and equally available to all network participants. Network operators which also act as content providers as well as market participants with strong market positions in particular must not have the possibility to discriminate content providers.
Keywords: L13; L51; L96; 330; net neutrality; efficiency; investment incentives